Tetrakis(μ(3)-9-oxa-10-boraanthracen-10-olato)tetrakis[(diethyl ether)lithium] - Franz, Daniel (International Union of Crystallography, 2011)
The title compound, [Li(4)O(4)(C(12)H(8)BO)(4)(C(4)H(10)O)(4)], features a Li(4)O(4) cube. Each Li atom in the cube is additionally coordinated by a diethyl ether molecule and each O atom in the cube carries a 9-oxa-10-boraanthracene residue. The crystal studied was a non-merohedral twin [twin law (-1 0 0 / 0 0 1 / 0 1 0); the contribution of the major twin component refined to 0.553 (3)] emulating apparent tetragonal symmetry, whereas the actual crystal system is just orthorhombic.